Ways To Digitize Service in the Conditions of a Digital Economy - Ogli, Usmonov Murodbek Dusmurot (LPPM STIE Krakatau, 2025)
Purpose: This study examines effective ways to digitize services in the context of a rapidly expanding digital economy and analyzes the role of digital infrastructure, financial technology, artificial intelligence, e-commerce platforms, and digital public services in transforming traditional service delivery models. Research methodology: This study employs a descriptive and analytical approach using secondary data from various sources to evaluate the relationship between digital transformation components, service development, and economic performance. Results: The findings indicate that digitalization is a structural transformation that requires the coordinated development of infrastructure, human capital, and institutions, whereas digital literacy and user competencies play a key role in driving service adoption and online engagement. Conclusions: Sustainable service digitization requires a balanced policy approach that integrates technological modernization with regulatory support and workforce reskilling to ensure long-term efficiency and inclusivity. Limitations: This study is limited by its reliance on secondary data and does not include primary empirical analyses at the micro-or organizational levels. Contribution: This study contributes to the literature by providing a comprehensive perspective on service digitization, emphasizing the importance of integrating technological, institutional, and human capital dimensions to support digital transformation and inclusive economic growth